Memories of the future: Educational technologies and goals of the enlightenment - Tatiana Ivanovna Luzina, Irina Alexandrovna Tulpe,; Anton Yakovlevich Kozhurin, Yulia Valerievna Puiu, Veda Igorevna Spivak, (Opción, 2019)
The study aims to investigate educational technologies and goals of the enlightenment via hermeneutical methodology. As a result, the spoken word of persuasion and communication is more important than a book, and practical enlightenment implemented in actions is more valuable than formal education. In conclusion, the search for Russian philosophical and pedagogical thought and the reasoning of religious dissidents as for the enlightenment are correlated with the challenges of the information society.